PARTISIPASI MASYARAKAT DALAM IMPLEMENTASI KEBIJAKAN VAKSINASI COVID-19 (Studi Kasus di Kecamatan Bogor Selatan, Kota Bogor) - Yuli Sri Kurnia; Rita Rahmawati; Faisal Tri Ramdani (LPPM Universitas Djuanda Bogor, 2022)
Some people still have not carried out the Covid-19 vaccination, indicating that the level of community participation in the implementation of the Covid-19 vaccination is not optimal. This study aims to analyze community involvement in the implementation of the Covid-19 vaccination policy. This descriptive research is used to describe or describe the data that has been collected in its entirety and reality. The research data were collected using interview, observation and questionnaire techniques which were then processed into numbers so that they could be used to conclude. The calculation results from this study for the community participation indicator obtained a score of 3.46 which was included in the Good category and for the policy implementation indicator, a score of 3.85 was categorized as Good due to community participation or participation such as participating in data collection on vaccination targets, participating in the Covid-19 vaccination program. , good communication between the sub-district / Covid-19 task force and the community, good and sufficient resources, and the attitude of the task force when conducting socialization, monitoring and evaluation make community participation good in the implementation of the vaccination program. However, some things must be improved, namely [1] conducting periodic socialization and counselling, considering that there are still people who do not want to be vaccinated. [2] monitoring and providing information related to vaccination information.